The Secret Explorers and the smoking volcano - King, SJ (King, SJ. Secret Explorers, 2021)
"Meet the Secret Explorers - a band of brainiac kids from all around the world. Everyone in this diverse group of young experts has a specialty, from outer space to dinosaurs, and each story follows a character who gets chosen for a "secret exploration". In this fun, fact-filled children's book, we join volcanoes expert Cheng on an exciting mission to Mount Yasur on the island of Vanuatu. Joined by biology expert Leah, the team are beyond excited to witness a real-life volcanic eruption. But soon, excitement turns to worry when they realize that people are in danger, and must stage a heroic rescue mission. Kids will love turning the pages to find out if the Secret Explorers manage to succeed in their mission!" --